Farmer-driven innovation: lessons from a case study of subterranean clover seed production. (28th March 2022) - Moss, Wesley M.; Nichols, Phillip G.H.; Foster, Kevin J.; Ryan, Megan H.; Guzzomi, Andrew L.
Abstract : Farmers are often overlooked and undervalued as sources of innovation, but can be powerful drivers of ingenuity and development. We evaluate historical developments in the Australian subterranean clover seed-production industry as a case study of farmer-driven innovation. Subterranean clover seed machinery patents (75% of which were patented by farmers) are analysed using conventional innovation frameworks, such as the theory of inventive problem solving (TRIZ), to extract lessons for supporting farmer-driven innovation. The small scale of this industry, compared with mainstream cereal-cropping industries and the isolation of farmers, provides analogous lessons for agriculture in developing countries. Economic drivers are important in enabling farmer innovation and the value proposition for developing new inventions must be clear to justify the time and expense. Farmers are different from firms and their on-farm knowledge and experience can form an essential part of innovation. Drivers of innovation also differ, with farmers less likely to attempt to commercialize inventions. Farmers can also be hesitant to share their inventions, instead holding them as trade secrets in competitive industries. Support and collaboration are needed from government and researchers to assist in commercialization or dissemination of useful innovations and to prevent knowledge from being confined to a localized farmer or region. Advances in agriculture require farmer input in research and development, but the benefits will be greater if farmers are enabled to be drivers of innovation.